TOXIC EFFECTS OF NONYLPHENOL ON OXIDATIVE STRESS IN TESTES AND EPIDIDYMIS OF ADULT ALBINO RATS - U. KANCHANA GANGA; B. KISHORI; P. SREENIVASULA REDDY (International Journal of Pharma and Bio Sciences, 2016)
The present study is aimed to investigate the toxic effects of nonylphenol on oxidative stress in testes and epididymis of adult albino rats. Randomly 32 healthy adult male rats were divided into 4 groups and each group with 8 animals. First group served as control, second, third and fourth groups were administered with nonylphenol at doses of 1 µg/kg bw, 10µg/kg bw and 100 µg/kg bw every alternative day for 55 days. After the treatment, on 57th day of experiment, animals were sacrificed and collected the tissues. The indices of testes and epididymis were significantly (p<0.05) decreased in nonylphenol treated rats than controls. In the testicular and internal parts of epididymis total lipid peroxidation levels were significantly (p<0.05) increased, whereas the activity levels of antioxidant enzymes such as superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase levels were decreased significantly (p<0.05) in nonylphenol treated rats when compared to the control group. DNA fragmentation was increased significantly in a dose dependent manner when compared to control. The present study concluded that exposure of male albino rats to nonylphenol at low concentrations induces oxidative stress in testes and epididymis of adult rats.